Diverse feto-maternal presentations of chorioangioma: a case series - Keragode Guruswamy, Amulya; Chaudhary, Mamta Kumari; Kumari, Snigdha; Rohilla, Minakshi; Saha, S. C.; Chaluvashetty, Sreedhara B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Placental chorioangioma is the most common benign non-trophoblastic tumor of the placenta, originating from primitive chorionic mesenchyme and typically being vascular. It has an incidence of 0.6-1% among all pregnancies. The size of the lesion remains the most important factor in prognosis, with small tumors often going unnoticed through the pregnancy without any fetal or maternal complications. Larger lesions (more than 4-5 cm) usually present early in pregnancy and can lead to significant maternal and fetal issues. Late presentation allows more time for fetal maturity and is associated with a lower perinatal mortality rate. Ultrasonography and color Doppler imaging are the main diagnostic tools for placental chorioangioma, showing hypo- and hyper-echoic lesions with vasculature connected to the fetal vascular system. Fetal complications, if they occur, may require intrauterine interventions. We present a series of four cases presenting at different gestational ages with diverse fetal and maternal clinical features and outcomes.